Tell me why: an ecological momentary assessment study of unknown substance use motives - DeFalco, Angelica, author; Emery, Noah N., advisor; Karoly, Hollis C., committee member; Riggs, Nathaniel R., committee member (Colorado State University. Libraries, 2025)
Theoretical models of motivations for substance use emphasize the role of contextual information (e.g., affect) when making decisions about use. These theories explicitly propose that there are moments during which individuals may make decisions about use outside of their conscious awareness. That is, decisions to use can happen quickly, without much thought (Cooper et al., 2015; McCarthy et al., 2010; Wiers et al., 2007). However, to our knowledge, no previous research has examined the frequency and phenomenology (i.e., its predictors and consequences) of this motivational state at the event level. This study sought to fill this gap in the literature by introducing an "I don't know" option to a substance use motive questionnaire (i.e., an unknown motive) assessed using ecological momentary assessment (EMA), a micro longitudinal research technique. The aims of this study included 1) characterizing the occurrences of unknown substance use motives, 2) investigating the prospective relationship between unknown substance use motives and affect, and 3) understanding the prospective association between unknown substance use motives and problems. We hypothesized that participants would endorse the unknown substance use motive and the endorsement of an unknown motive would be more likely at high and low levels of affect (both positive and negative), indicating a potential quadratic relationship. We also hypothesized that an unknown substance use motive endorsement would be associated with experiencing more problems. Results demonstrated that the probability of unknown motive endorsement varied as a function of previous moment affect, such that lower (-1SD) and higher levels (+1SD) of negative affect were associated with an increased probability of endorsing "I don't know" compared to mean levels of negative affect. In contrast, mean levels of positive affect were associated with higher probabilities of endorsing "I don't know" compared to lower and higher levels of positive affect. No association was found between "I don't know" motive endorsement and number of problems. Results confirm a non-linear association of affect demonstrated in previous studies and suggest unique patterns of awareness for use motivation across the affective valences. Results also continue to highlight the pivotal role of affect in substance use at the moment-level. This study was innovative in both method and concept, leveraging EMA's strengths to investigate a fleeting and dynamic process that may inform future intervention efforts aimed at changing use patterns. Future research should continue to investigate this phenomenon to better understand its impact on functioning and develop prevention and intervention strategies.
Keywords: affect; substance use; substance use motives; decision making; addiction; substance use consequences